Eu imaginado: as selfies como representação de si no Instagram - Rodrigues, Antonia Zeneide (2021)
The incorporation of digital information and communication technologies in our social environment makes us give new meanings to several aspects of our daily lives, and has corroborated the emergence of new ways of experiencing time and space. The recording of selfportraits through smartphone front cameras and their dissemination on digital social media made available on mobile phone applications led to the popularization of "selfies", digital photographs of oneself, but also the adoption of public attitudes and social behaviors that they correspond to the constant registration and dissemination of self-images. In this sense, we have followed since 2018 the trajectory of self-images on Instagram through the “selfie” hashtag, aiming to realize the possibility of representing oneself through selfies posted on Instagram in the form of “imagined selves”. More specifically, understanding the meaning attributed to the selfie in people's daily lives, and realizing the redefinition of the “image self” shown on the platform, in addition to reflecting on the importance attributed to the search for visibility and approval by people. In other words, to notice among those surveyed the use of subterfuges representing the self in Intagram. As support for the investigation, theoretical reflections and articulations with empiricism, we use Morin (2012; 2014) as a way to support some concepts related to image; Norval Baitello (2010; 2014; 2019) from the perspective of an iconophagic society, and especially in the discussion about selfies; Le Breton (2012;2013) for understanding the social context of redefinition of the body itself, among others. In this context, we realized through the empirical-methodological research that the selfies anchored in Intagram enable a representative image of oneself, taking into account its countless possibilities of clippings, filters, editions, made possible by the tool. There is, thus, through the records, the search for achieving desired and/or imagined ideals of oneself that materialize in the registration and publication of self-images.